ANALISIS PERBANDINGAN MAKNA PERIBAHASA YANG MENGANDUNG KATA ARAH "TIMUR, SELATAN, BARAT, UTARA" DALAM PERIBAHASA MANDARIN DAN INDONESIA - Aritonang, Christine Sri Rejeki; Ina, Ina; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Direction words are very commonly used in daily life, so words expressing location such as "east, south, west, north" also appear in Chinese idioms. Direction words can be combined to form different idioms. There are also idioms involving location words in Indonesian, but not many. This study analyzes the idioms related to the four directions of "east, south, west, and north" in idioms to understand the meanings, and also helps learners to better understand the cultural differences between the two idioms. This article collects 69 Chinese idioms and 6 Indonesian idioms. The result of the study is that the Chinese idioms containing the location words "east, south, west, north" are more idioms expressing behavior. Indonesian idioms are more idioms indicating the direction of behavior. Idioms with two morphemes used together are more common in Chinese idioms, while idioms with one morpheme in Indonesian idioms are more common. In addition, it was found that one Indonesian idiom and one Chinese idiom had almost the same interpretation and meaning.